Relation of antifactor-Xa peak levels and venous thromboembolism after trauma. Issue 6 (December 2017) - Karcutskie, Charles A.; Dharmaraja, Arjuna; Patel, Jaimin; Eidelson, Sarah A.; Martin, Arch G.; Lineen, Edward B.; Namias, Nicholas; Schulman, Carl I.; Proctor, Kenneth G.
Abstract : BACKGROUND: No previous studies have established the optimal antifactor Xa (anti-Xa) level to guide thromboprophylaxis (TPX) dosing with enoxaparin in trauma patients. We hypothesize that achieving 0.2–0.4 IU/mL anti-Xa will decrease venous thromboembolism (VTE) rates after trauma. METHODS: This was a retrospective review of 194 intensive care unit patients sustaining blunt or penetrating trauma from January 2015 to March 2017. All received initial enoxaparin (30 mg BID subcutaneous) and mechanical devices for TPX. Peak anti-Xa levels were drawn after each third dose. The enoxaparin dose was adjusted up to a maximum of 60 mg BID subcutaneous until a peak level of 0.2–0.4 IU/mL was achieved. Data are expressed as mean ± SD if parametric or median (IQR) if not. RESULTS: The Greenfield Risk Assessment Profile score was 9 ± 4, Injury Severity Score 23 ± 14, and hospital length of stay 19 (11–38) days. The overall VTE rate was 7.2% (n = 14), with 10 deep venous thromboses (DVT) and 5 pulmonary emboli (PE). One patient had both a DVT and PE. The median time to VTE diagnosis was 14 (7–17) days. In those diagnosed with a VTE, 50.0% (n = 7) never reached 0.2–0.4 IU/mL anti-Xa and 42.8% (n = 6) were diagnosed with a VTE after achieving these levels. Prophylactic levels were achieved initially in 64 (33.0%) patients, and achieved later in 38 (19.6%) additional patients, giving an overall prophylactic rate of 52.6% (n = 102). There were no differences in VTE (6.9% vs. 7.6%, p = 0.841), DVT (3.9% vs. 6.5%, p = 0.413), or PE (3.9% vs. 1.1%, p = 0.213) rates between those who became prophylactic and those who did not. CONCLUSIONS: There was no difference in VTE incidence between those achieving anti-Xa peak levels of 0.2–0.4 IU/mL and those who did not. Furthermore, these levels were never achieved in some trauma patients despite repeated dosing over a >10-day period. LEVEL OF EVIDENCE: Therapeutic study, level IV.